Building Information Modelling (BIM) adoption and implementation enablers in AEC firms: a systematic literature review. (2nd November 2021) - Abbasnejad, Behzad; Nepal, Madhav Prasad; Ahankoob, Alireza; Nasirian, Araz; Drogemuller, Robin
ABSTRACT: Building Information Modelling (BIM) has gained much attention in recent years, as both a new innovation and methodology. Many architecture, engineering and construction (AEC) firms have reported significant competitive advantages following its implementation. Despite the variety of benefits that BIM offers, its potential has not yet been fully realised. A key reason for this can be located in the difficulties of implementation at the organisational level; a process that demands significant changes in organisational business structure. However, there exists little extensive study on the analysis and synthesis of the literature surrounding organisational BIM implementation. This paper presents a systematic literature review (SLR) on studies from 2004 to July 2019 to allow for a thorough synthesis of the existing BIM literature, innovation management, and information technology domains to identify BIM adoption and implementation enablers. Of the 80 selected studies, 27 enablers were identified to contribute to a more comprehensive utilisation of BIM at the organisational level. These included strategic initiatives, cultural readiness, learning capacity, knowledge capability and IT leveragability, network relationships, process and performance management, and change management practices. The role each implementation enabler has in IT-equipped innovations generally and to BIM implementation specifically is discussed throughout. The results of this paper seek to aid AEC firms in gauging the organisational readiness of the implementation process as well as the required interventions and capability development for successful BIM implementation overall.